2014
DOI: 10.3390/e16031571
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Discriminatory Power of DEA Using Shannon’s Entropy

Abstract: Abstract:In many data envelopment analysis (DEA) applications, the analyst always confronts the difficulty that the selected data set is not suitable to apply traditional DEA models for their poor discrimination. This paper presents an approach using Shannon's entropy to improve the discrimination of traditional DEA models. In this approach, DEA efficiencies are first calculated for all possible variable subsets and analyzed using Shannon's entropy theory to calculate the degree of the importance of each subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Bian and Yang [39] extend the Shannon-DEA procedure to establish a comprehensive efficiency measure for appraising DMUs' resource and environment efficiencies. Xie et al [40] employ Shannon entropy theory to calculate the degree of the importance of each DMU. Then they combined the obtained efficiencies and the degrees of importance to improve the discrimination of traditional DEA models.…”
Section: Introductionmentioning
confidence: 99%
“…Bian and Yang [39] extend the Shannon-DEA procedure to establish a comprehensive efficiency measure for appraising DMUs' resource and environment efficiencies. Xie et al [40] employ Shannon entropy theory to calculate the degree of the importance of each DMU. Then they combined the obtained efficiencies and the degrees of importance to improve the discrimination of traditional DEA models.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Soleimani-Damaneh and Zarepisheh's research, some other literature [25][26][27][28][29][30][31][32] can be found where the DEA method is also combined with Shannon's entropy. However, as there are a great many different DEA models, then the selection of DEA models would have a great effect on the results of the entropy DEA model.…”
Section: Dea With Shannon's Entropymentioning
confidence: 99%
“…Based on this first research, Bian and Yang [25] proposed an extension to the resource and environment efficiency analysis of the provinces in China. More recently, Xie et al [26] proposed an extension research of [24] in which different variable subsets were considered. Similarly, Wu et al [27] proposed a method for aggregating cross-efficiency with Shannon's entropy and they also extended their research in [28].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating Shannon entropy into DEA has attracted the interests of a number of scholars [44][45][46]. In this section, Shannon entropy is utilized to calculate the weights of interval cross-efficiency.…”
Section: The Cross-efficiency Model Based On Shannon Entropymentioning
confidence: 99%